Preface - Kuncevičius, Albinas; Žilinskaitė, Agnė (Archaeologia Lituana, 2024)
In the annual journal of scientific articles Archaeologia Lituana 24 (2023) of the Department of Archaeology of Vilnius University we present the more important and interesting archaeological research of our colleagues as well as a chronicle of the Department’s works and scientific activities of the year 2023. Archaeologia Lituana 23 (2022) was dedicated to the 100th anniversary of the birth of the archaeologist and pioneer of archaeomythology Marija Birutė Alseikaitė-Gimbutienė (Gimbutas, 1921–1994), and most of the articles published in the volume were based on the papers presented at the international scientific conference “The New Old Europe”. In this issue of Archaeologia Lituana 24, assoc. prof. dr. Algimantas Merkevičius provides an analysis of the scientist’s works and their significance in the study of Baltic origins which you can find in his article “Marija Gimbutienė and the theory of Baltic origins”. Lithuanian archaeologists’ usually study various objects from prehistoric to historic and modern times. This diversity of research is also reflected in the variety of published articles: from the Iron Age burial site in Vilkija to the study of the Vilnius pharmacies of the interwar period of the 20th century, from the Egyptian crocodile mummy in the National Museum of Lithuania to the Soviet genocide crimes, murders and torture, which are particularly important in the geopolitical context of the present. Archaeologia Lituana is also a chronicle of the annual work of the Department of Archaeology of Vilnius University. The year 2023 was a particularly important year. In the spring, we received the evaluation report of the Study field of Archaeology by the Centre for Quality Assessment in Higher Education (SKVC). The expert panel consisted of prof. dr. Jean-Luc Lamboley (panel chairperson), prof. dr. Raguel Pique Huerta (member of academic community), Sigita Mikšaitė (member representative of social partners), and Tautvydas Gaižauskas (students’ representative), evaluated the programme very positively: “The two curricula (bachelor and master) demonstrate a good balance between history and archaeology, between theory and practice, and give a complete overview of all the disciplines linked to the archaeological field, included archaeometry. A particular attention is paid to the Landscape Archaeology which is a promising discipline in the field. [...] The collaboration with the faculty of medicine is excellent, master students have access to specialized laboratories and can carry out their research work (final thesis) in optimal conditions by benefiting from highly qualified supervisors. By this way rare subjects archaeozoology or archaeobotanical can be taught only in Vilnius university. [...] The high scientific and pedagogical qualification of the teaching staff is to be underlined“. At the beginning of 2023, the European Research Council (ERC) awarded prof. dr. Giedrė Motuzaitė Matuzevičiūtė Keen, a bioarchaeologist at Vilnius University, a grant of €2 million for her research project “Past and Future Millet Foodways”. Prof. dr. G. Motuzaitė Matuzevičiūtė Keen became the first national researcher to receive an ERC established investigator grant under Horizon Europe and the third to receive an ERC grant overall. On 19–20 October 2023, the 12th international scientific conference Readings of Jonas Puzinas with the title “Strategies and Methods of Archaeological Research”, organized by the Department of Archaeology of Vilnius University, was held. The conference reports and any other articles prepared by fellow archaeologists are welcome and will be published in the next edition of Archaeologia Lituana in 2024.